2021
DOI: 10.1186/s41235-021-00329-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoracial disparities in cognition are associated with multiple socioeconomic status-stress pathways

Abstract: Systemic racism can have broad impacts on health in ethnoracial minorities. One way is by suppressing socioeconomic status (SES) levels through barriers to achieve higher income, wealth, and educational attainment. Additionally, the weathering hypothesis proposes that the various stressful adversities faced by ethnoracial minorities lead to greater wear and tear on the body, known as allostatic load. In the present study, we extend these ideas to cognitive health in a tri-ethnic sample of young adults—when cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Hence we also performed a multivariable logistic regression to use all available data. Although sociodemographic and comorbidity factors are interconnected with race and ethnicity as a result of structural racism and systemic inequality within the US, 42,43 these were treated as independent variables in the logistic regression model. Although we found lower proportions and odds of amyloid PET positivity for Asian and Hispanic participants, Black participants had significantly lower odds but no difference in proportion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence we also performed a multivariable logistic regression to use all available data. Although sociodemographic and comorbidity factors are interconnected with race and ethnicity as a result of structural racism and systemic inequality within the US, 42,43 these were treated as independent variables in the logistic regression model. Although we found lower proportions and odds of amyloid PET positivity for Asian and Hispanic participants, Black participants had significantly lower odds but no difference in proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Hence we also performed a multivariable logistic regression to use all available data. Although sociodemographic and comorbidity factors are interconnected with race and ethnicity as a result of structural racism and systemic inequality within the US, these were treated as independent variables in the logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…A key area for future investigation will be to examine how socioeconomic conditions create a context of biopsychosocial vulnerability and influence the risk of dementia at critical periods throughout the life course, including early and mid‐life. When considered within a historical context of structural racism that manifested as policy‐sanctioned residential segregation and concentrated impoverishment of racial and ethnic minorities, 54 these results strongly implicate neighborhood socioeconomic conditions as a means by which racial and ethnic differences in dementia risk are health inequities.…”
Section: Discussionmentioning
confidence: 99%
“…US-born Hispanics show lower cognitive function when compared with US-born non-Hispanic Whites and foreign-born Hispanics (79). Adverse socioeconomic environments can impact US-based Hispanics' cognitive health through limited access to educational and occupational opportunities, psychosocial stress, and systemic racism (80). Additionally, studies have shown US-based Hispanics are at higher risk of developing hypertension, obesity, and T2D, all of which can impair cognitive health (81).…”
Section: Discussionmentioning
confidence: 99%